Guidelines for contributors (2010)
PROFILE Issues in Teachers’ Professional Development This journal is led by the PROFILE research group at Departamento de Lenguas Extranjeras -Universidad Nacional de Colombia, Sede Bogotá. It is a publication for teachers of English interested in increasing their professional expertise. Starting from the assumption that our professional knowledge is enriched by different members of our academic community, the journal is mainly concerned with sharing the results of classroom research projects undertaken by primary and secondary school teachers as well as teachers of adults. It also includes articles written by teacher educators and guest teachers willing to disseminate innovations and research findings. PROFILE is registered in Ulrich’s Periodicals Directory, Latindex, and the Directory of Open Access Journals –DOAJ. It is indexed in the MLA International Bibliography, Educational Research Abstracts online (ERA), Linguistics and Language Behavior Abstracts database (LLBA), SciELO, and Publindex-Colciencias, classified in category A2.